The Effect Of Price Earning Ratio, Current Ratio, Net Profit Margin And Debt To Equity Ratio On Stock Prices Of The Lq-45 Index Of The Indonesia Stock Exchange 2016-2018 - Ahmad Solihin; Afrizal; Lilik Sulistyowati (International Journal of Science, Technology & Management, 2021)
This study aims to analyze the joint and partial effect of the price earning ratio, current ratio, net profit margin, and debt to equity ratio variables on the stock prices of companies listed on the LQ-45 Index of the Indonesian Stock Exchange for the 2016-2018 period. The research sample is companies that fall into the LQ-45 stock category, namely 45 companies for the 2016-2018 period using normality, autocorrelation, multicollinearity, and heteroscedasticity tests as classical assumptions using multiple regression analysis methods. The results of the analysis show that the research variable has a significant effect on stock prices in companies in the LQ-45 Index category of the Indonesian stock exchange for the 2016-2018 period and the partial test results show that the price earning ratio variable has no significant effect on stock prices, the current variable ratio and affects stock prices. net profit margin significantly affects stock prices and the debt to equity ratio variable significantly affects stock prices in companies in the LQ-45 Index category of the Indonesian stock exchange for the period 2016 - 2018.